Level of Quality of Service for Diesel Train of Surabaya-Sidoarjo Line Based on Servqual Method (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2023)
Surabaya City as one of the metropolitan cities in Indonesia, serves as the centre of social and economic activities in East Java. The problem of housing makes these workers choose to live in satellite areas. In addition to road transport, movement from satellite areas such as Sidoarjo to Surabaya also uses rail transport. This study aims to determine the expected value and reality value of passengers on the Minimum Service Standards (MSS) of Diesel Train (KRD) Surabaya - Sidoarjo Line. As well as knowing the condition of SPM Diesel Train (KRD) Surabaya - Sidoarjo Line based on the dimensions expected by passengers. In this study using the servqual method obtained from surveys on passengers to optimise the level of public satisfaction. The result is that the measurable evidence dimension indicator has an expected value of 3.64 while the reality value is 3.32. In the reliability dimension, the expected value is 3.60 while the reality value is 3.48. The dimension of responsiveness has an expected value of 3.55 compared to the reality of 3.21. The guarantee dimension has an expected value of 3.64, for a reality value of 3.33. Finally, in the empathy dimension, the expected value is 3.45 while the reality value is 3.19. The Actual Servqual Score figure is 92%. This shows that the overall fulfilment of the Surabaya-S Sidoarjo KRD service has met 92% of passenger expectations compared to before using the train.